DISADVANTAGES AND PROBLEMS OF THE INSTITUTIONAL ENVIRONMENT IN THE FIELD OF PUBLIC GOVERNANCE OF REGIONAL DEVELOPMENT IN UKRAINE - SYTNYK, YEVHEN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Effective state management of regional development is one of the main conditions for creating a favorable investment environment, one of the criteria for the country's success in the implementation of comprehensive reforms in various fields. State regional policy is closely linked to investment processes in Ukraine.Since 2014, several attempts have been made in Ukraine to modernize public administration of regional development. Within the framework of this governmental course, significant institutional transformations have been carried out and a number of normative legal acts have been adopted. However, Ukraine has not yet developed an effective institutional system that would ensure optimal use of national economic potential and achieve at least average European living standards.The urgency and priority of the problem is due to the fact that the investment attractiveness of national economies is increasingly determined by the quality of the institutional environment, the ability to innovate through the use of institutional features of society. The state of public administration institutions is an important component of a favorable investment climate, affects the well-being of citizens and regional development, and must be brought into line with the needs of large-scale reforms and new regional policies.The changes in the institutional environment of regional development in Ukraine over the past decade are shown: creation of the legal field and new institutions. The growth of transaction costs of consumers of public administration services is considered. It is shown why modern Ukraine still remains in an institutional trap and why the transition to an effective institutional environment and to investment-friendly environment is complicated. It is proposed to improve the institutional and regulatory policy in the field of public administration of regional development in Ukraine: restraining the process of creating new institutions, clear delineation of their functionality, increase of own incomes of local budgets, reducing the number of existing regulations.
Keywords: institutional innovations; institutional environment; transaction costs; overload by institutions; institutional congestion; regional development